2018 Integrated Communications, Navigation, Surveillance Conference (ICNS) 2018
DOI: 10.1109/icnsurv.2018.8384881
|View full text |Cite
|
Sign up to set email alerts
|

L-band Digital Aeronautical Communications System (LDACS) flight trials in the national German project MICONAV

Abstract: Today's voice-based air-ground communication system for aircraft guidance is suffering from increasing saturation of the VHF band in high density areas. Therefore the European Union strives for a transition from analog voice communication to more spectrum efficient digital communication. This transition shall be realized, among others, through the development and implementation of the L-band Digital Aeronautical Communications System (LDACS). In order to verify the suitability of LDACS for both communications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The concept was proven in theory in 2012 with simulations in 2013 showing achievable accuracy of the aircraft position of around 4m [22]. Later in 2013 and 2015, flight trials confirmed the localization accuracy of around 15m with demonstration equipment, while in 2019 it was set out in the German national project MICONAV [15] to test real-time positioning. All of the aforementioned steps confirm, that LDACS can be used as a true navigation substitute for En-Route (ENR) continental flights in case of DME or GPS outage.…”
Section: E Extension Towards Navigation and Surveillancementioning
confidence: 96%
“…The concept was proven in theory in 2012 with simulations in 2013 showing achievable accuracy of the aircraft position of around 4m [22]. Later in 2013 and 2015, flight trials confirmed the localization accuracy of around 15m with demonstration equipment, while in 2019 it was set out in the German national project MICONAV [15] to test real-time positioning. All of the aforementioned steps confirm, that LDACS can be used as a true navigation substitute for En-Route (ENR) continental flights in case of DME or GPS outage.…”
Section: E Extension Towards Navigation and Surveillancementioning
confidence: 96%
“…In addition, the L-band Digital Aeronautical Communications System (LDACS) completes the FCI by supporting both air-ground (A/G) and air-to-air (A2A) communications using the LDACS A/G and LDACS A2A communication modes, respectively. Whereas the LDACS A/G mode is already fully developed, has been demonstrated in flights trials in March/April 2019 in the MICONAV project [2], and is currently undergoing the standardization process of the International Civil Aviation Organization (ICAO), the LDACS A2A mode is currently being developed within the German national project IntAirNet.…”
Section: Introductionmentioning
confidence: 99%